New advances in the development of sarcoidosis models: a synopsis of a symposium sponsored by the Foundation for Sarcoidosis Research - Sellares, Jacobo; Strambu, Irina; Crouser, Elliot D; Freudenberg, Marina A; Gulati, Mridu; Hart, Simon; Herzog, Erika; Kolb, Martin; Weichhart, Thomas; Drake, Wonder P; Spitzer, Ginger; Culver, Daniel A (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2018)
Sarcoidosis is a complex disease with variable phenotypes that will require a multisystem approach to understand pathophysiology. One of the most challenging problems in sarcoidosis research is the absence of valid and widely accepted experimental models that accurately simulate human disease. The Foundation of Sarcoidosis Research (FSR) has funded five projects for the development of novel experimental models for sarcoidosis, presented and discussed in a workshop organized during the European Respiratory Society Congress held in Milan from September 9th to 13th. The experimental, in vivo or in sillico models presented may be quite helpful for investigating specific pathogenic and therapeutic questions, addressing especially severe forms of sarcoidosis.